Perlindungan Hukum oleh Pemerintah dalam Kegiatan Pinjaman Online dan Arisan Online - Yunita Dian Ashari; Nayla Sarachenita Arssya (Fakultas Hukum Universitas Islam Indonesia, 2024)
Economic activity is shifting towards electronic transactions over time. This development has resulted in lending and borrowing activities, as well as social gatherings that were previously carried out in person but are now more convenient to do online. Technological advancements enable quick and easy access to cash funds online, and they are simple to manage. However, this convenience has significant social and economic consequences, including the emergence of new security and regulatory challenges. Online lending and social gatherings have significant social and economic implications, but they also present security and regulatory challenges. Further research is required to understand the legal relationship and resolution of legal consequences that arise during the implementation of online lending and online social gathering activities, because many debtors are unable to pay, and many social gathering participants are trapped in fictional social gatherings. This study considered the prevalence of crime in online economic activities such as online loan transactions and online social gathering transactions. Because there is no binding legal protection for organisers of online economic transaction activities, many people have fallen victim to these crimes. Consequently, concerns were raised about how online loan transactions and online social gathering transactions are community economic activities, as well as the existence of regulations and state protection for their practice in society. The answer will be investigated through normative legal research, which will employ both a statutory and a case approach based on engagement and legal protection theories. Finally, debtors and social gathering participants require guarantees, which can take the form of protection institutions or insurance.